The Effect of Physical Exercise on Depression in College Students: The Chain Mediating Role of Self-Concept and Social Support - Zhang, Junliang; Zheng, Shuang; Hu, Zhongzheng (Frontiers in Psychology, 2022)
Objective This study introduced self-concept and social support as research variables to establish a research mechanism, in order to encourage college students to participate in sports better, relieve or overcome depression. Methods The survey was conducted among 1,200 college students in Jiangxi, China. Serial mediation models were used to examine whether self-concept and social support mediated in the effect of physical exercise on depression. Results Physical exercise significantly negatively predicted college depression. Moreover, Self-concept and social support mediate the relationship between physical exercise and depression in college students. Conclusion This study reveals how physical exercise affects college students’ depression and its mechanism, and the results have certain enlightenment significance for maintaining and promoting college students’ physical and mental health.